На службі Батьківщині та психології: науково-дослідна, організаційно-практична та науково-педагогічна діяльність професора О.В. Тімченка - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Оніщенко, Наталія Вікторівна; Оніщенко, Н. В.; Онищенко, Наталья Викторовна; Onishchenko, Nataliia V.; Приходько, Ігор Іванович; Приходько, І. І.; Приходько, Игорь Иванович; Prykhodko, Ihor I. (К. : Вид-во НУОУ, 2017)
Дана стаття є спробою надання можливості знайомства наукової спільноти з головними досягненнями видатного вченого сучасної України, доктора психологічних наук, професора Тімченка Олександра Володимировича. У статті проведено аналіз найбільш значущих наукових і прикладних результатів діяльності професора О.В. Тімченка в межах екстремальної та кризової психології, а також психології діяльності в особливих умовах; представлено огляд наукових досліджень, що виконані під його керівництвом; охарактеризовано основні вектори його науково-практичної діяльності; наведено опис його наукової школи.

Данная статья является попыткой предоставления возможности знакомства научного сообщества с главными достижениями выдающегося ученого современной Украины, доктора психологических наук, профессора Тимченко Александра Владимировича. В статье проведен анализ наиболее значимых научных и прикладных результатов деятельности профессора А.В. Тимченко в рамках экстремальной и кризисной психологии, а также психологии деятельности в особых условиях; представлен обзор научных исследований, выполненных под его руководством; охарактеризованы основные векторы его научно-практической деятельности; приведено описание его научной школы.

The article is an attempt to enable the broad scientific audience familiar with the results of long-term and highly fruitful research, organizational, scientific and practical teaching activities of a prominent specialist in legal psychology and psychology of activities in special environments, Doctor of Psychology, Professor O. V. Timchenko. Due to the great scientific research and publishing heritage of O. V. Timchenko, which contains dozens of books, training manuals and hundreds of articles, in the article are given separate and the most significant scientific and practical Professor achievements, provided analysis of the most significant steps in his academic life. The beginning of the path of the scientist began by the research on the issues of psychological readiness of a military specialist to emergency action in a state of emotional stress. This vector became the determining factor in academic research of Professor O. V. Timchenko. Subsequently, he theoretically and empirically substantiated and proved that psychological readiness is the most important quality of individual specialists of extreme activities and outlined the main directions of reducing their combat and psyhohen losses of personnel of the high risk units. Professor O. V. Timchenko is the one among the first in the national psychology described the state of high professional and psychological readiness for immediate and highly efficient actions of the specialists of extreme professions and offered scientific and methodological principles of formation of their psychological stability (stress resistance). One of the most important acquisitions of modern psychology was the dissertation of O. V. Timchenko for the degree of Doctor of Psychology on "Professional stress of Ukrainian police officers (conceptualization, prognostication, diagnosis and correction)." This scientific work and monographs of O. V. Timchenko, which concerned mentioned issues, is one of the most cited publications in the field of extreme psychology. In the field of activities of the police specialists, Professor O. V. Timchenko designed a formula for success ratio and scale of individual extremeness; proposed a number of scientific, methodological and practical developments, including rapid diagnosis method to determine the types of nervous system of police officers with posttraumatic stress disorder, conceptual approaches and principled position on the organization and providing of psychological support to police officers. Professor O. V. Timchenko also initiated a series of researches in the field of the psychological support of the specialists of extreme professions, including rescue workers. He was the one who started his research and practice in the field of the establishment of methodological principles of modern crisis and extreme psychology and psychology of activity in specific environments. With the participation of the Professor, the work on the development and formation of the psychological service of Internal Troops of the Ministry of Internal Affairs of Ukraine, of the National Guard of Ukraine and their scientific support continues. The article provides information regarding scientific school of the Doctor of Psychology, Professor O.V. Timchenko. During the period of his activity in the field of science, he became the scientific adviser of more than a dozen postgraduates and doctoral students, both candidate and doctoral degrees. Under his supervising still ongoing the most interesting and most relevant studies that meet the needs of modern psychology activities in special environments. In addition, he is the founder of the Research Laboratory of Extreme and Crisis Psychology – the unit, which activities are directed to implementing the main tasks of extreme crisis and psychology, as well as ensuring fruitful interaction of psychologists of the extreme activities of all military forces and law enforcement agencies of Ukraine.
Лефтеров В. О. На службі Батьківщині та психології: науково-дослідна, організаційно-практична та науково-педагогічна діяльність професора О. В. Тімченка / В. О. Лефтеров, Н. В. Оніщенко, І. І. Приходько // Вісник Національного університету оборони.– Вип. 1(48). – К. : Вид-во НУОУ,2017. – С. 135-142.
Keywords: наукові досягнення; наукова школа; екстремальна психологія; кризова психологія; психологія діяльності в особливих умовах; научные достижения; научная школа; экстремальная психология; кризисная психология; психология деятельности в особых условиях; scientific achievements; scientific school; extreme psychology; crisis psychology; psychology of activity in special conditions; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology